The effect of mindful breathing exercise on stress levels of nursing first year students before first clinical experience - Akman, Özlem; Yıldırım, Dilek; Öksüz, Sena; Poplata, Sena Öksüz (Gevher Nesibe Sağlık Araştırmaları Merkezi, 2020)
Aim: Clinical practices, which are an integral part of nursing education, create serious stress especially in first year nursing students. It is important to control the pre-clinical stress that nursing students experience. This study aimed to examine whether breath therapy is effective on the pre-clinical experience stress levels of first year nursing students. Methods: Semi-experimental in single group pre- post-test study design. 42 nursing first year students were included in the study. Before the application, Student Information Form, Visual Analog Scale and Pagana Clinical Stress Questionnaire were applied to all students. Then 30 minutes by expert researcher. breath therapy was applied and questionnaires were applied again. This process is performed once a week for a total of 3 times 30 minutes. repeated as. Results: The average age of the students was 19.13±.92. According to VAS, the stress level experienced by the students before the clinical practice was 6.77 ± 1.64, whereas it was determined as 2.64±2.06 after the third application. The mean clinical stress score before the application was 28.60±10.13 and after the third application it was 16.37±9.08. When the mean scores of the Clinical Stress Questionnaire of the students were compared separately according to the measurements, it was seen that their stress decreased in all measurements made before the application of breath therapy. Conclusion: With this study, conscious breathing therapy application was found to be effective in reducing the stress of nursing students who will go to the clinic for the first time.

Amaç: Hemşirelik eğitiminin ayrılmaz bir parçası olan klinik uygulamalar, özellikle birinci sınıf hemşirelik öğrencilerinde ciddi düzeyde stres yaratır. Hemşirelik öğrencilerinin yaşadığı klinik öncesi stresi yönetmek önemlidir. Bu çalışmada, bilinçli farkındalık nefes terapi uygulamasının birinci sınıf hemşirelik öğrencilerinin ilk klinik öncesi deneyim öncesi stres düzeyleri üzerinde etkili olup olmadığı araştırıldı. Yöntem: Tek grup ön test-son test çalışma tasarımında yarı deneysel olarak 42 hemşirelik birinci sınıf öğrencisinin katılımıyla gerçekleştirildi. Başvuru öncesinde tüm öğrencilere Öğrenci Bilgi Formu, Görsel Analog Skala ve Pagana Klinik Stres Anketi uygulandı. Uzman araştırmacı tarafından 30 dakika nefes terapi uygulaması gerçekleştirildi. Haftada bir kez toplam 3 hafta süresince gerçekleştirildi. Her uygulamaya 30 dakika devam edildi. Uygulama sonrası ölçümler tekrarlandı. Bulgular: Öğrencilerin yaş ortalaması 19.13 ± .92'dir. VAS'a göre, nefes terapi uygulaması öncesi öğrencilerin yaşadığı stres düzeyi 6.77 ± 1.64 iken, nefes terapi üçüncü uygulaması sonrası stres düzeyinin 2.64 ± 2.06 ‘ya düştüğü belirlendi. Uygulama öncesi ortalama klinik stres skoru 28.60 ± 10.13 ve üçüncü uygulamadan sonra 16.37 ± 9.08 idi. Öğrencilerin Klinik Stres Anketinin ortalama puanları ölçümlere göre ayrı ayrı karşılaştırıldığında, nefes terapisi uygulanmadan önce yapılan tüm ölçümlerde streslerinin istatistiksel olarak anlamlı düzeyde azaldığı görüldü. Sonuç: Bu çalışma ile ilk kez kliniğe gidecek
Hemşirelik birinci sınıf öğrencilerinde bilinçli fakındalık nefes egzersizinin ilk klinik uygulama stresine etkisi
Keywords: Breath therapy; Mindfulness; Clinical stress; Nursing students; Nefes terapi; Bilinçli farkındalık; Klinik stres; Hemşirelik öğrencileri